A new ultrasound score for the assessment and follow-up of chronic pancreatitis: The 'Gemelli USCP score'. Issue 6 (June 2020) - Pagliari, Danilo; Ainora, Maria Elena; Brizi, Maria Gabriella; Cintoni, Marco; Rinninella, Emanuele; Attili, Fabia; Mancarella, Francesco A.; Garcovich, Matteo; Riccardi, Laura; Pompili, Maurizio; Gasbarrini, Antonio; Manfredi, Riccardo; et al.
Abstract: Background: : Ultrasound (US) is frequently the first line imaging technique used in patients with abdominal pain and clinical suspicion of chronic pancreatitis (CP), but its role in the diagnosis and follow-up of CP is still controversial. Aims: : We aimed to develop a dedicated score for the US staging of CP and to evaluate the agreement of this score with standard imaging techniques. Methods: : Ninety consecutive patients with a diagnosis of CP referred to the pancreatic outpatient clinic of A. Gemelli Hospital between June and September 2018 were recruited in the study. Patients underwent pancreatic US to evaluate different morphological parameters to develop an US based score system, called the Gemelli UltraSound Chronic Pancreatitis (USCP) score. Results: : The Gemelli USCP score significantly increased according to the Cambridge score for both mean value ( p <0.0001) and each parameter evaluated ( p <0.0001). Moreover, we found a significant correlation between the score and laboratory parameters related to pancreatic exocrine insufficiency such as vitamin D, B9, and B12 deficiency and fecal elastase values ( p <0.0001). Conclusions: : The development of a dedicated US score could be useful in the follow up of patients with CP as alternative non-invasive technique to standard radiological imaging.